Citizenship and Mental Health Policy in Europe - Pauline Prior (Social Work & Society, 2007)
The problems confronted by people who experience mental disorders are often conceptualised in terms of health and illness. However, these problems extend far beyond the healthcare system, into all areas of human life. Having a psychiatric diagnosis may have a negative impact on every aspect of the individual's life, leading to the deprivation or limitation of rights in relation to housing, employment, and family life. In this article, some of these problems are discussed within the theoretical framework of debates on citizenship and on human rights. As the context is Europe, reference is made to the recent policy initiatives with the EU, to national and European level consumer organisations and to cases brought before the European Court of Human Rights.